CORRELATION BETWEEN FAILURES IN THE PRE-ANALYTICAL PHASE AND INCREASED LABORATORY COSTS (Interdisciplinary Studies Journal, 2026)
This study aims to analyze the correlation between failures in the pre-analytical phase and the increase in laboratory costs in clinical analysis laboratories, highlighting the impacts on result quality and the financial sustainability of institutions. This is an Integrative Literature Review conducted in the SciELO, LILACS, Google Scholar and PubMed, databases from March to May 2026. Descriptors related to the pre-analytical phase, laboratory errors, quality control, and laboratory costs were used, combined with the Boolean operator AND. Studies published between 2022 and 2026, available in full text, in Portuguese and English, and directly addressing pre-analytical failures and their operational or economic impacts were included. Editorials, letters to the editor, and studies not directly related to the topic were excluded. After applying the eligibility criteria and full-text reading, 13 studies composed the final sample. The analysis showed that the pre-analytical phase concentrates most laboratory errors, especially failures in sample identification, inadequate patient preparation, improper transport, and lack of process standardization. These non-conformities result in recollections, rework, waste of supplies, and increased turnaround time for test results. In addition to direct costs, indirect impacts were observed, such as diagnostic delays, prolonged hospital stays, and increased healthcare workload. Studies indicate that structured quality management programs significantly reduce the incidence of these failures. It is concluded that there is a direct correlation between failures in the pre-analytical phase and increased laboratory costs, making investment in preventive strategies essential to ensure safety, efficiency, and institutional sustainability.
Keywords: Quality Control; Costs and Cost Analysis; Laboratories